2020
DOI: 10.3892/br.2020.1291
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in glutathione, nitric oxide and 3‑nitrotyrosine levels following exercise and/or hyperbaric oxygen treatment in mice with diet‑induced diabetes

Abstract: Oxidative stress is involved in the development of diabetes. Nitric oxide (NO) contributes to oxidative stress, affects the synthesis of glutathione (GSH) in tissues and also regulates important physiological processes. The levels of nitrosative stress, assessed by measuring the levels of 3-nitrotirosina (3NT) as well as the bioavailability of NO are modulated by exercise and hyperbaric oxygenation (HBO). The aim of the present study was to evaluate the effects of exercise and HBO on the levels of NO, 3NT and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 58 publications
(70 reference statements)
2
5
0
Order By: Relevance
“…We were able to show an accumulation of protein-bound 3-nitrotyrosine and 4-HNE modified proteins in the high-fat fed mice. This was also observed in B6 mice on a HFD by Gutiérrez-Camacho et al [ 35 ], although additional challenges were applied in the study. Both protein modifications have been previously shown in HFD-induced stress [ 36 , 37 ] and aging [ 14 , 38 , 39 ].…”
Section: Discussionsupporting
confidence: 73%
“…We were able to show an accumulation of protein-bound 3-nitrotyrosine and 4-HNE modified proteins in the high-fat fed mice. This was also observed in B6 mice on a HFD by Gutiérrez-Camacho et al [ 35 ], although additional challenges were applied in the study. Both protein modifications have been previously shown in HFD-induced stress [ 36 , 37 ] and aging [ 14 , 38 , 39 ].…”
Section: Discussionsupporting
confidence: 73%
“…Excessive ROS production is known to suppress antioxidant defense systems and physical exercise training has been shown to upregulate antioxidant defense mechanisms in several tissues and metabolic disorders ( Golbidi et al, 2012 ; Lima et al, 2015 ). Glutathione, an abundant endogenous antioxidant has been reported to be decreased in type 2 diabetic patients ( Sekhar et al, 2011 ; Lagman et al, 2015 ; Gutiérrez-Camacho et al, 2020 ). In our study, we observed a decrease in the GSH pool in the GK rat tissues, which increased significantly with exercise.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, excessive NO production can disturb the physiological balance between the generation of peroxynitrite, antioxidant defense mechanisms, and signaling pathways involving NO in different tissues. 50 In this study, a high fructose consumption caused an oxidative state in the offspring's liver, demonstrated by an increase in NO and a low content of sulfhydryl. Although these changes (NO and SH) were more present at the dose of 10%/l of fructose, we can take into account that both doses caused DNA damage and that despite this difference was not statistically significant at both doses in relation to the control group, we observed that, regardless of the dose, fructose can cause this imbalance in the offspring.…”
Section: Discussionmentioning
confidence: 60%
“…The same results were observed by Vitaglione et al, 49 in which an imbalance in oxidative stress affected the transcription of numerous biochemical mediators, which led to of modulation the tissue and cellular events, such as apoptosis, necrosis and fibrosis, which in turn are present in different types of liver diseases. A study by Gutiérrez-Camacho et al 50 using diet-induced diabetes showed an increase in NO content and elevated levels of nitrosative stress, suggesting that any increased elimination of NO by superoxide is offset by an increase in its production in this animal model. Furthermore, excessive NO production can disturb the physiological balance between the generation of peroxynitrite, antioxidant defense mechanisms, and signaling pathways involving NO in different tissues.…”
Section: Discussionmentioning
confidence: 69%